Immune Correlates of Diffuse Myocardial Fibrosis and Diastolic Dysfunction Among Aging Women With Human Immunodeficiency Virus. (17th May 2019) - Zanni, Markella V; Awadalla, Magid; Toribio, Mabel; Robinson, Jake; Stone, Lauren A; Cagliero, Diana; Rokicki, Adam; Mulligan, Connor P; Ho, Jennifer E; Neilan, Anne M; Siedner, Mark J; Triant, Virginia A; et al.
Abstract: Human immunodeficiency virus (HIV) imparts increased heart failure risk to women. Among women with HIV (WHIV), immune pathways relating to heart failure precursors may intimate targets for heart failure prevention strategies. Twenty asymptomatic, antiretroviral-treated WHIV and 14 non-HIV-infected women matched on age and body mass index underwent cardiac magnetic resonance imaging and immune phenotyping. WHIV (vs non-HIV-infected women) exhibited increased myocardial fibrosis (extracellular volume fraction, 0.34 ± 0.06 vs 0.29 ± 0.04; P = .002), reduced diastolic function (diastolic strain rate, 1.10 ± 0.23 s -1 vs 1.39 ± 0.27 s -1 ; P = .003), and heightened systemic monocyte activation. Among WHIV, soluble CD163 levels correlated with myocardial fibrosis ( r = 0.53; P = .02), while circulating inflammatory CD14 + CD16 + monocyte CCR2 expression related directly to myocardial fibrosis ( r = 0.48; P = .04) and inversely to diastolic function ( r = –0.49; P = .03). Clinical Trials Registration . NCT02874703. Abstract : Antiretroviral-treated women with HIV (WHIV) exhibit increased myocardial fibrosis and decreased diastolic function compared with non-HIV-infected women. Among WHIV, the degree of CCR2 expression on circulating inflammatory CD14 + CD16 + monocytes relates directly to myocardial fibrosis and inversely to diastolic function.